중년여성의 약물사용 실태 조사 - 신혜숙; 강경인; 김경숙; 김은경; 김은숙; 김희선; 이영선; 신성희; 최지선; 황선기; Shin, Hye-Suk; Kang, Kyung-In; et al. (여성건강간호학회지, 2001)
The purpose of this study was to investigate the drug use of middle aged women. The subject consisted of 330 middle aged women who ranged in age from 40 to 60 years. They were selected in Seoul. Kyung-Ki province, Korea. Data were collected by using guestionnaires, from April, 10th to 30th 2001 and analyzed by the SPSS PC+ program using qui-square The results are summarized as follows : 1. The proportion of drinking and smoking experience was 42.4%, 3.7%. The motivation of drug use was advised family and relatives (46.1%), doctor's order(39.4%), magazine and advertisement(14.5%). Most of middle aged women get the information on knowledge of drug from hospital (47.3%), magazines and advertisement(30.3%), advised family and relatives(22.4%). And 57.9% of the middle aged women didn't know side effect of the using drug and 13.9% of the middle aged women have had experienced with side effect. And the level of attitude on drug abuse in middle aged women was 43%. Most of the subjects(93.9%) didn't use alternative drugs, and they used more than 3 kinds of drugs(47%). 2. They used digestives(44.2%), applying ointments (41.8%), drinks (39.4%), analgesics (39.1%), laxatives(8.8%), anti hypertension drugs (33%), and anti-anemic drugs(8.8%) in their orders.